Fruit based synthesis of silver nanoparticles-an effect of temperature on the size of particles - Chauhan, Shalini; Upadhyay, Mukesh Kumar (Recent Research in Science and Technology, 2012)
The cost effective and eco-friendly technique for synthesis of silver nanoparticles from the extract of seed of P.granatum. The reduction process was simple and convient to handle and was monitored by UV-vis spectroscopy. So the green synthesis of silver nanoparticles from 1mM AgNO3 solution was prepared through the extract of P. granatum seed which act as a capping and reducing agent. The morphology and uniformity of silver nanoparticles were invastigated by TEM and EDX. The functional group of protein molecule was using identified by FTIR. Increase in temperature leads increase in size of silver nanoparticles.